A comparative study of selected strength parameters of university and national level male wrestlers and judokas - Prasad, A.; Cruz, L. D.; Mohare, M.; Harshe, N. G.; Sankar, U. V. (International Journal of Physical Education, Sports and Health, 2024)
The purpose of this study was to find out the difference between selected strength parameters such as grip strength, shoulder strength, back strength, core strength and leg strength of university and national level male wrestlers and judokas. To accomplish this study 30 male university and national level players (15 from wrestling and 15 from judo) were selected from Kerala. The selected strength variables such as grip strength, shoulder strength, back strength, core strength and leg strength taken for this study were measured using hand-grip strength dynamo meter, pull up test, back-leg strength dynamometer and sit up test respectively. Independent t-test was computed to compare the variables. To test the hypothesis the significance level was set at 0.05 percent. The outcome reveals that there is a statistical significant difference between grip strength, shoulder strength, core strength, leg strength and there is no statistical significant difference between back strength of university and national level male wrestlers and judokas.